Length–weight relationships for three freshwater fish species from the Pengxi River (a tributary of the Yangtze River, China). (4th September 2017) - Chen, X. W. J.; Zhu, Q. G.; Li, S.; An, M.
Summary: This study determined the length–weight relationships of three freshwater fish species [ Culter oxycephaloides (Kreyenberg & Pappenheim, 1908), Squalidus argentatus (Sauvage & Dabry de Thiersant, 1874), Rhodeus sinensis (Günther, 1868)] from Pengxi River, a tributariy of Yangtze River of China. Fish were collected during 2016 using drift gill nets (mesh size 1, 2 and 3 cm) and cage net (0.5 cm mesh size). For Culter oxycephaloides had no previous length–weight estimates were reported in the science literature. For Squalidus argentatus the present estimate includes a new maximum total length while for Rhodeus sinensis our study confirms the only existing LWR estimate quite well.